Effect of Canal Irrigation on Water Table -A Case Study - Vishwakarma, S K; Tiwari, Y K; Kale, V K (Journal of Agricultural Engineering, 2001)
A study on water table fluctuation due to canal irrigation was conducted at one of the minor commands of left bank canal of Rani Awanti bai Sagar Pariyojana, Jabalpur. A total of 30 open wells were selected within the command and monthly ground water balancing was carried out using ground water model to estimate the fluctuation in water table due to recharge. The result shows that during post monsoon, water table was close to the surface and the average water table depth in irrigation period was 1.35 below ground level. The estimated recharge and thus monthly water table fluctuation in irrigation period were observed positive. The result shows the alarming situation of water table rise in the command, which may be controlled by adopting preventive measures to avoid the complex problems of waterlogging, soil salinity etc.